Tensiomyographic assessment of contractile properties in elite youth soccer players according to maturity status - Padrón-Cabo, A.; Corredoira, F. J.; Lorenzo-Martínez, M.; González-Víllora, S.; Rey, E. (Journal of Human Kinetics, 2023)
Little is known about how muscle contractile properties are affected by biological maturation in elite youth soccer players. This study aimed to determine the effects of maturation on contractile properties of rectus femoris (RF) and biceps femoris (BF) muscles assessed by tensiomyography (TMG) and provide reference values for elite youth soccer players. One hundred twenty-one elite youth soccer players (14.98 ± 1.83 years; 167.38 ± 10.37 cm; 60.65 ± 11.69 kg) took part in the study. The predicted peak height velocity (PHV) was used in order to establish players` maturity status (Pre-PHV, n = 18; Mid-PHV, n = 37; Post-PHV = 66). Maximal radial displacement of the muscle belly, contraction time, delay time, and contraction velocity for RF and BF muscles were recorded. One-way ANOVA showed no significant differences between PHV groups for any tensiomyography variables in RF and BF muscles (p > 0.05). Our results established that maturity status did not show a significant effect in mechanical and contractile properties on RF and BF muscles evaluated by TMG in elite youth soccer players. These findings and reference values can be useful for strength and conditioning coaches of elite soccer academies in order to optimize the evaluation of neuromuscular profiles.